2022
DOI: 10.3390/met12101658
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Tool Rotational Speed on Physical and Chemical Properties of Dissimilar Friction-Stir-Welded AA5083/AA6060 Joints

Abstract: Aluminum alloys have been successfully used in the railroad and automotive industries because of their potential to significantly reduce component weights, and their good mechanical and anti-corrosion properties. Problems with joining aluminum alloys are characterized by low weldability, which influences the need for studies focused on unconventional methods. The environmentally friendly and low-cost friction-stir-welding method enables the material to be joined without melting. In the following study, dissimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Several studies on FSW involve dissimilar aluminum alloys [31,131]. Ghaffarpour et al [132] join dissimilar aluminum alloys of 5083-H12 in the retreating side and 6061-T6 in the advancing side, changing the rotational speed (i.e., 700, 1600, 2500 rpm) in combination, respectively, with the pin diameter (i.e., 2, 3, 4 mm), the shoulder diameter (i.e., 10, 12, 14 mm), and the traverse speed (i.e., 25, 212.5, 400 mm/min).…”
mentioning
confidence: 99%
“…Several studies on FSW involve dissimilar aluminum alloys [31,131]. Ghaffarpour et al [132] join dissimilar aluminum alloys of 5083-H12 in the retreating side and 6061-T6 in the advancing side, changing the rotational speed (i.e., 700, 1600, 2500 rpm) in combination, respectively, with the pin diameter (i.e., 2, 3, 4 mm), the shoulder diameter (i.e., 10, 12, 14 mm), and the traverse speed (i.e., 25, 212.5, 400 mm/min).…”
mentioning
confidence: 99%
“…This study revealed that when spindle speed and feed rate increase simultaneously, agitation offers less frontal resistance due to uniform heat distribution during processing. The increase in spindle speed and feed rate will directly increase the heat generation, thus causing smooth material flow [34][35]. Due to this process, the softening material under the tool shoulder caused by the frictional heat after plunging increases the plasticisation of the material, thus helping the material to mix and stir during the joining process.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Particularly, welding of Al alloys by FSW can be widely seen in the scientific literature [11][12][13]. Different Al alloys which belong to magnesium, aluminum and copper systems were also successfully joined with Al5083 alloy by FSW [14][15][16][17][18]. In FSW, tool design which is governed by the selection of tool dimensions including shoulder to pin diameter ratio, dimensions of pin, shoulder profile, pin profile etc influence the success of the welding process [19].…”
Section: Introductionmentioning
confidence: 99%